Optimalisasi Penguatan Profil Pelajar Pancasila (P5) Melalui Gelar Karya sebagai Penerapan Nilai Pancasila di SMK NU 1 Sukodadi - Winda Safitri; Frischa Vera Yunida; Yanuangga Galahartlambang; Agustinus Salukh; Tri Winarsih (Pusat Riset dan Inovasi Nasional, 2025)
The Pancasila Student Profile Strengthening Project (P5) aims to develop students who possess strong character and skills that are relevant to the demands of the times, particularly in facing global challenges and technological advancements. One of the implementations of P5 at SMK NU 1 Sukodadi is the Gelar Karya activity, which serves as a platform for students to showcase their creativity and apply the values of Pancasila in real life. The theme of this activity is